2014
DOI: 10.1002/2014gl059722
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time measurements of the concentration and isotope composition of atmospheric and volcanic CO 2 at Mount Etna (Italy)

Abstract: We present unprecedented data of real-time measurements of the concentration and isotope composition of CO 2 in air and in fumarole-plume gases collected in 2013 during two campaigns at Mount Etna volcano, which were made using a laser-based isotope ratio infrared spectrometer. We performed approximately 360 measurements/h, which allowed calculation of the δ 13 C values of volcanic CO 2 . The fumarole gases of Torre del Filosofo (2900 m above sea level) range from À3.24 ± 0.06‰ to À3.71 ± 0.09‰, comparable to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
84
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(91 citation statements)
references
References 28 publications
7
84
0
Order By: Relevance
“…(Geldern et al, 2014;Rizzo et al, 2014). The stability of measurements of the total concentration and the δ 18 O of CO 2 were assessed prior to the gas exchange measurements by analysing the contents of an air cylinder for 22.5 h (Fig.…”
Section: Incubation System and Gas Analysismentioning
confidence: 99%
“…(Geldern et al, 2014;Rizzo et al, 2014). The stability of measurements of the total concentration and the δ 18 O of CO 2 were assessed prior to the gas exchange measurements by analysing the contents of an air cylinder for 22.5 h (Fig.…”
Section: Incubation System and Gas Analysismentioning
confidence: 99%
“…A recent application of IRIS at Mount Etna by Rizzo et al (2014) demonstrated the precision and accuracy of these measurements. Those authors described two campaigns performed in 2013 that involved the first real-time measurements of the CO 2 concentration and δ 13 C in the ambient air and in fumarolic gases emitted in the area of Torre del Filosofo (TDF) at Mount Etna.…”
Section: Introductionmentioning
confidence: 99%
“…If rising levels of atmospheric CO 2 during the time period shown in Fig. 1.7c had been due primarily to volcanoes, atmospheric CO 2 would have been expected to have gotten isotopically heavier (Rizzo et al 2014), which is the opposite of what has been observed.…”
Section: Carbon Dioxidementioning
confidence: 81%